2021
DOI: 10.1016/j.gpb.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Alterations in COVID-19

Abstract: Since the outset of the coronavirus disease 2019 (COVID-19) pandemic, the gut microbiome in COVID-19 has garnered substantial interest, given its significant roles in human health and pathophysiology. Accumulating evidence is unveiling that the gut microbiome is broadly altered in COVID-19, including the bacterial microbiome, mycobiome, and virome. Overall, the gut microbial ecological network is significantly weakened and becomes sparse in patients with COVID-19, together with a decrease in gut microbiome div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 88 publications
9
73
0
Order By: Relevance
“…belong to the same phylum as a critically important constituent of the gut microbiome and common ingredient of probiotics, Bifidobacterium . Bifidobacterium abundance is known to decrease in SARS-CoV-2-infected subjects, as seen in ours and other studies ( Tao et al, 2020 ; Xu et al, 2020 ; Reinold et al, 2021 ; Yeoh et al, 2021 ; Zuo et al, 2021 ; Hazan et al, 2022b ). We have anecdotally observed, through our clinical experiences pre and post Fecal Microbiota Transplant, that certain bacteria in the same phylum may be able to replace each other’s function.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…belong to the same phylum as a critically important constituent of the gut microbiome and common ingredient of probiotics, Bifidobacterium . Bifidobacterium abundance is known to decrease in SARS-CoV-2-infected subjects, as seen in ours and other studies ( Tao et al, 2020 ; Xu et al, 2020 ; Reinold et al, 2021 ; Yeoh et al, 2021 ; Zuo et al, 2021 ; Hazan et al, 2022b ). We have anecdotally observed, through our clinical experiences pre and post Fecal Microbiota Transplant, that certain bacteria in the same phylum may be able to replace each other’s function.…”
Section: Introductionsupporting
confidence: 88%
“…Ours and other data also support a protective role of Bifidobacterium in SARS-CoV-2 infection, possibly through these immune functions of Bifidobacterium . Our study and others ( Tao et al, 2020 ; Xu et al, 2020 ; Reinold et al, 2021 ; Yeoh et al, 2021 ; Zuo et al, 2021 ; Hazan et al, 2022b ) show that the gut microbiome, particularly Bifidobacterium levels, relates to positivity and severity of SARS-CoV-2 infection. Tao et al (2020) showed that changes in gut microbiota composition might contribute to SARS-CoV-2-induced production of inflammatory cytokines in the intestine, which may lead to the cytokine storm onset.…”
Section: Discussionsupporting
confidence: 72%
“…Increased stress-, inflammation-, and virulence-associated gene expression was observed, suggesting that these viruses play a role in the host immune response to SARS-CoV-2 infection [29]. Moreover, after disease resolution, delayed SARS-CoV-2 viral shedding and persistent gut virome dysbiosis were noted [74]. Immune dysregulation driven by SARS-CoV-2 infection may also promote imbalance of the microbial and viral ecosystems of the human body that could result in long COVID or post-acute sequelae of COVID-19 [70].…”
Section: The Virome and Human Diseasementioning
confidence: 96%
“…One limitation of the study was the relatively small sample used but we plan to extend our research to bigger cohorts. Importantly, we excluded from our analysis patients who had a history of COVID-19, considering that SARS-CoV-2 infection significantly alters the gut microbiome [ 81 ]. Given the heterogeneity in the overall microbial composition observed in the participants, further recruitment would enable the detection of additional correlations between gut microbiota and MetSyn and T2DM pathogenesis.…”
Section: Discussionmentioning
confidence: 99%